The use of synthetic oligonucleotides as hybridization probes. II. Hybridization of oligonucleotides of mixed sequence to rabbit beta-globin DNA. - Wallace, R B (1981)
Two oligonucleotides 14-bases long were synthesized, one complementary to rabbit beta-globin DNA (R beta G14A) and the other with the same sequence except for a single base change (T for C) (R beta G14B). Hybridization conditions were established such that R beta G14A would hybridize to globin DNA while R beta G14B would not. We also synthesized a mixture of 13-base long oligonucleotides (R beta G13Mix), representing eight of the possible coding sequences for amino acids 15-19 of rabbit beta-globin. One of the eight is complementary to globin DNA. R beta G13Mix was found to hybridize specifically to globin DNA under conditions where oligonucleotides forming single base pair mismatches do not. Furthermore, R beta G13Mix was shown to hybridize specifically to colonies containing a plasmid with a globin DNA insert. These results are discussed with respect to a general procedure for screening recombinant clones for those containing DNA coding for a protein of known amino acid sequence.